ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸š2016 å±Šå¦ç”Ÿå¯¹è¿‘ä¹‰è¯ â€œå¿½ç„¶â€ä¸Žâ€œçªç„¶â€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Kurnianingsih, Endah; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractâ€œHuranâ€ and â€œ Turanâ€ have same word meaning that showed an incident which fast and unexpected. Students of Mandarin Language are often false when use these two words, so there are always a mistake when they want to use it. In this research, the author use Test Method to collect the data, to know about level of mastery and level of difficulty to these synonym words â€œHuranâ€ and â€œTuranâ€ by the mandarin language programme students batch 2016 in faculty of teacher education and education science tanjungpura university. The result of this research shows that from 28 participants there is 56% students have pretty good mastery on synonym â€œHuranâ€ and there is 55% students have pretty good mastery on synonym â€œTuranâ€. The result of this paper show that in studying both of that lexicon, students have been mastered the usage of word very well, but, there is still students that do not mastering well. The usage of synonym â€œHuranâ€ with primely level lies on the usage for verb orÂ adverb, while the mastered synonym â€œTuranâ€ with primely level lies on the usage as predicate. When analyze the difficulties, the writer find that students have trouble in mastering the usage of synonym â€œHuranâ€ is â€œHuranâ€ may be repleced before subject. And, there is 2 difficultiesÂ in mastering â€œTuranâ€ word, include the use of â€œTuranâ€may be use as complement and â€œTuranâ€ is placed before â€œ no + nounâ€. The cause of many students find mistake is insufficient mastery of knowledge and rules for using these two words. Based on study above can be conclude the mandarin language programme students batch 2016 in faculty of teacher education and education science tanjungpura university. mastery in synoym â€œHuranâ€ and â€œTuranâ€ is passably.Â KeyWord : synonym, huran, turanÂ